Phase II clinical trial of pazopanib in patients with acute myeloid leukemia (AML), relapsed or refractory or at initial diagnosis without an intensive treatment option (PazoAML) - Keßler, Torsten; Müller-Tidow, Carsten (Annals of hematology, 2019)
We evaluated pazopanib (800 mg orally QD) in patients not eligible for intensive treatment with relapsed/refractory AML or at initial diagnosis. Patients receiving pazopanib for > 14 days were analyzed for safety, tolerability, and efficacy. Co-primary endpoints were cumulative response rate and reduction of bone marrow microvessel density. Twenty patients (median age 76 years, range 52-86) were treated. Fifteen had relapsed/refractory and five had newly diagnosed AML. Median ECOG performance status was 1 (range 1-3). Four patients had adverse, 15 intermediate, and 1 patient favorable cytogenetic/molecular risk (ELN 2010 criteria). The safety profile of pazopanib was as reported. The most common adverse events of any grade were gastrointestinal. Two patients achieved PR (blast reduction > 50%), 14 stable disease (SD), and 4 progressive disease. Median PFS was 65 days (95% CI 29-105). After the end of the study, 1 CRi and 1 CRp occurred on demethylating agents, and 1 CR upon alloSCT. In these patients, SD and improved general condition on pazopanib allowed therapy escalation. Median OS for the overall study population was 191 days (95% CI 87-435) and 1-year survival was 35%. There was no significant change in microvessel density. Clinical trial information: NCT01361334.
Gesehen am 14.06.2019